2017
DOI: 10.1007/s11064-017-2339-0
|View full text |Cite
|
Sign up to set email alerts
|

The protection of novel 2-arylethenylquinoline derivatives against impairment of associative learning memory induced by neural Aβ in C. elegans Alzheimer’s disease model

Abstract: Cerebral deposition of amyloid β-peptide (Aβ), a fundamental feature of Alzheimer's disease (AD), damages the neurocytes and impairs the cognition functions and associative learning memory of AD patients. A series of novel 2-arylethenylquinoline derivatives were synthesized and evaluated in our previous study, which inhibited Aβ aggregation in vitro effectively at the concentration of 20 μmol/L and exhibited high antioxidant activity. In order to verify the capacity of anti-AD in vivo, the transgenic Caenorhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Additionally, the CL2355 strain overexpresses human Aβ when grown at 22°C and develops paralysis, but grows normally at 16°C (Ahmad and Ebert, 2020 ). CL2355 is a good model for measuring AD-like chemotactic cognition/memory behaviors compared to the CL2122 strain, which shows normal chemotaxis (cognition/memory; He et al, 2017 ). Interestingly, Fenchol treatment significantly increased the lifespan in the CL2006 and CL4176 strains and reduced Aβ accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the CL2355 strain overexpresses human Aβ when grown at 22°C and develops paralysis, but grows normally at 16°C (Ahmad and Ebert, 2020 ). CL2355 is a good model for measuring AD-like chemotactic cognition/memory behaviors compared to the CL2122 strain, which shows normal chemotaxis (cognition/memory; He et al, 2017 ). Interestingly, Fenchol treatment significantly increased the lifespan in the CL2006 and CL4176 strains and reduced Aβ accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans has impressive chemotaxis behavior. To analyze whether C. elegans use chemotaxis to avoid SDG, we performed chemotaxis assays (see Figure 1(d) ) using synchronized late L4 larvae or young adult wild-type N2 worms as described previously [ 18 , 19 ]. About 200 worms were placed in the center of an assay NGM plate (diameter: 3.5 cm), which contain 50, 200, or 500 μ M of SDG plus 2% tetramisole hydrochloride to paralyze the worms on one side of the plate (A side) and H 2 O as solvent control plus 2% tetramisole hydrochloride on the opposite side of the plate (B side).…”
Section: Methodsmentioning
confidence: 99%
“…Lublin et al found that caffeine, tannic acid and bacitracin could protect C. elegans CL2006 strain from Aβ induced toxicity [ 50 ]. He et al used C. elegans CL2355 as an Alzheimer disease model to test the neuroprotective activities of seven new 2-arylvinylquinoline derivatives [ 51 ]. C. elegan s is maintained at a low temperature.…”
Section: Discussionmentioning
confidence: 99%